Oligonucleotide-based Preconditioning of DCD Cardiac Donors and Its Impact on Cardiac Viability. Issue 12 (December 2019) - Kearns, Mark J.; Miller, Sally D.; Kong, Hyejin J.; Sirounis, Demetrios; Cheung, Anson; Bashir, Jamil; Seidman, Michael A.; Boyd, John H.
Abstract : Background: While clinical donation after circulatory death (DCD) cardiac transplantation is being implemented with increasing frequency to address the supply/demand mismatch of donor grafts, no research to date has examined a strategy of donor preconditioning to optimize the viability of DCD hearts for transplantation. In our rat model of the DCD protocol, we investigate the impact of pretreating donors with phosphorothioate-linked cytosine and guanine rich oligodeoxynucleotides (CpG ODN) and their effects on cardiac function, injury, and a novel left ventricular (LV) mRNA biomarker panel. Methods: DCD rats were subjected to a withdrawal protocol, followed by 20 minutes of warm acirculatory standoff, representing a group of severely injured hearts as previously demonstrated. Beating heart controls and DCD rats were pretreated with vehicle or stimulatory CpG ODN (beating heart control and DCD stimulated with CpG ODN, BST and DST ). Hearts were harvested for ex situ heart perfusion (ESHP), where LV function, histochemical injury, and differences in gene expression were characterized between groups. Results: Donor pretreatment with CpG ODN doubled the number of functional DCD hearts at ESHP. Pretreatment was associated with improved systolic and diastolic LV function, a reduction in histological injury, and markedly reduced elaboration of cardiac troponin-I in coronary effluent during ESHP. Pretreatment was also associated with a reduction in mRNA biomarkers associated with myocardial injury. Conclusions: A single dose of CpG ODN was associated with reduced biomarkers of cardiac injury and a 100% increase in cardiac viability in this rodent model of marginal DCD cardiac donation.